SUPERVISION AS A STRATEGY FOR MONITORING AND EVALUATION OF FAMILY HEALTH TEAM PRACTICES - Michela Macedo Lima Costa; Marília Santos Fontoura (Universidade Federal do Paraná, 2012)
This study aimed to describe the process of supervision developed by the Primary Care Coordination Group in relation to the Family Health teams' work in the Bahian Southwest. This research, carried out in 2008, has a qualitative approach, using the technique of triangulation of the information resulting from a documental survey, interviews, and from a focus group with the professionals. It may be seen that supervision benefits closeness and the establishing of links with aspects favorable to the development and evaluation of the work process. In this study, the activity of supervision was shown as a management tool which requires planning, involvement, interaction, continuity, and co-responsibility. In this sense, it is important that it should be constructed in a joint effort between managers, health professionals and service users.